Cruelty or humanity challenges, opportunities and responsibilities. - Rees, Stuart (POLICY Press, 2020)
Stuart Rees exposes politicians' fascination with cruelty in their deliberations about policies. Through empirical analysis, human stories and poetic commentary, he identifies non-destructive exercise of power, courageous public action and compelling humanitarian alternatives as the key to achieving a future in which dignity and equality flourish.